EFFECT OF COUNSELING ON KNOWLEDGE ATTITUDE AND BEHAVIOR OF TEXTILE INDUSTRY WORKERS ABOUT NIHL - Armabar Dwipantara Sasongko; Dwi Marliyawati; Kanti Yunika; Zulfikar Naftali (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Noise Induce Hearing Loss (NIHL) is a work accident which has a high incidence rate of workers ini the manufacturing industry nowadays. Attitudes and obedience behavior of manufacturing workers in using personal noise protective equipments are influenced by their knowledge about NIHL. Providing information such as health education periodically is needed to increase worker’s knowledge to change their attitudes and behaviors in order to obey safety regulations and using personal noise protective equipments.Objective: This study examines the effect of providing health counseling on the knowledge, attitudes, and behaviors of textile industry workers regarding noise induce hearing loss.Methods: This research method used quasi-experimental research method, with a one group pretest-posttest as design approach. Intervention of this research was a health counseling and the research instruments were leaflets, modules, and lectures about noise induced hearing loss. The subjects of this study were 35 workers of textile factories. Consecutive sampling were used to get subjects. Data on the level of knowledge, attitudes, and behavior were obtained through questionnaires before intervention and two weeks after the intervention was carried out. This research was located in one of the textile factories in Semarang Regency in 2020. Statistical analysis used Wilcoxon test, Fisher test, and Kolmogorov-Smirnov test.Results: The result of this research show that there was an increase in the mean score of subjects’s knowledge, attitudes and behavior. Statistical analysis show that that there is a significant differences between knowledge scores (p value = 0,000), attitudes scores (p value = 0,000), and behavior scores (p value = 0.024) before and after being given health education.Conclusion: The mean score of knowledge, attitudes and behavior of workers after being given information about noise induced hearing loss is higher than the average score of knowledge, attitudes and behavior of workers before being given a counseling.